2000
DOI: 10.1200/jco.2000.18.5.956
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose 5-Aza-2′-Deoxycytidine, a DNA Hypomethylating Agent, for the Treatment of High-Risk Myelodysplastic Syndrome: A Multicenter Phase II Study in Elderly Patients

Abstract: We were able to confirm our previous observation that DAC therapy was effective in half of the studied patients with high-risk myelodysplastic syndrome and is especially active in the patients with the worst prognoses. Myelosuppression was the only major adverse effect observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
281
2
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 529 publications
(298 citation statements)
references
References 19 publications
4
281
2
11
Order By: Relevance
“…While other methylation inhibitors like zebularine are known, most data are available for 5-Aza-CdR in terms of its clinical utility. Two phase II clinical studies have reported promising therapeutic activity of 5-Aza-CdR (decitabine) for patients with MDS 3 or CML. 4 Two other studies, enrolling mostly patients with AML, reported good response rates after decitabine treatment.…”
mentioning
confidence: 99%
“…While other methylation inhibitors like zebularine are known, most data are available for 5-Aza-CdR in terms of its clinical utility. Two phase II clinical studies have reported promising therapeutic activity of 5-Aza-CdR (decitabine) for patients with MDS 3 or CML. 4 Two other studies, enrolling mostly patients with AML, reported good response rates after decitabine treatment.…”
mentioning
confidence: 99%
“…In a multicenter, Phase II study, Wijermans et al treated 66 elderly patients (median age, 66 years) with decitabine 45 mg/m 2 daily (15mg/m 2 intravenously over 4 hours every 8 hours) for 3 days every 6 weeks. 104 Twenty-five patients had high IPSS risk scores. Overall, 49% of patients responded (CR, 20%; PR, 4%; hematologic improvement, 24%), and the response rate was 64% in the high-risk group.…”
Section: Epigenetic Therapymentioning
confidence: 99%
“…27 Decitabine has been investigated in elderly patients with MDS. 28 In a study of 66 patients with MDS, decitabine was administered at a dose of 45 mg/m 2 per day for 3 days every 6 weeks for a maximum of 6 cycles. 28 The overall response rate was 49%.…”
Section: Hypomethylating Agents (Decitabine and 5-azacytidine)mentioning
confidence: 99%
“…28 In a study of 66 patients with MDS, decitabine was administered at a dose of 45 mg/m 2 per day for 3 days every 6 weeks for a maximum of 6 cycles. 28 The overall response rate was 49%. Patients who had an International Prognostic Scoring System (IPSS) high-risk score had a response rate of 64%.…”
Section: Hypomethylating Agents (Decitabine and 5-azacytidine)mentioning
confidence: 99%
See 1 more Smart Citation